Assessment of the level of agreement in the interpretation of plain radiographs of lumbar spondylosis among clinical physiotherapists in Ghana - Bello, A.I.; Ofori, E.K.; Alabi, O.J.; Adjei, D.N. (BMC Medical Imaging, 2014)
Objective physical assessment of patients with lumbar spondylosis involves plain film radiographs (PFR) viewing and interpretation by the radiologists. Physiotherapists also routinely assess PFR within the scope of their practice. However, studies appraising the level of agreement of physiotherapists' PFR interpretation with radiologists are not common in Ghana.Method: Forty-one (41) physiotherapists took part in the cross-sectional survey. An assessment guide was developed from findings of the interpretation of three PFR of patients with lumbar spondylosis by a radiologist. The three PFR were selected from a pool of different radiographs based on clarity, common visible pathological features, coverage body segments and short post production period. Physiotherapists were required to view the same PFR after which they were assessed with the assessment guide according to the number of features identified correctly or incorrectly. The score range on the assessment form was 0-24, interpreted as follow: 0-8 points (low), 9-16 points (moderate) and 17-24 points (high) levels of agreement. Data were analyzed using one sample t-test and fisher's exact test at α = 0.05.Results: The mean score of interpretation for the physiotherapists was 12.7 ± 2.6 points compared to the radiologist's interpretation of 24 points (assessment guide). The physiotherapists' levels were found to be significantly associated with their academic qualification (p = 0.006) and sex (p = 0.001). However, their levels of agreement were not significantly associated with their age group (p = 0.098), work settings (p = 0.171), experience (p = 0.666), preferred PFR view (p = 0.088) and continuing education (p = 0.069).Conclusions: The physiotherapists' skills fall short of expectation for interpreting PFR of patients with lumbar spondylosis. The levels of agreement with radiologist's interpretation have no link with year of clinial practice, age, work settings and continuing education. Thus, routine PFR viewing techniques should be made a priority in physiotherapists' continuing professional education. © 2014 Bello et al.
Keywords: Agreement; Clinical physiotherapists; Interpretation; Plain radiographs